2010
DOI: 10.1007/s10549-010-0971-3
|View full text |Cite
|
Sign up to set email alerts
|

Classical membrane progesterone receptors in murine mammary carcinomas: agonistic effects of progestins and RU-486 mediating rapid non-genomic effects

Abstract: In this article, we demonstrate the expression of functional progesterone binding sites at the cell membrane in murine mammary carcinomas that are stimulated by progestins and inhibited by antiprogestins. Using confocal immunofluorescence, ligand binding and cell compartment-specific western blots, we were able to identify the presence of the classical progesterone receptors. Medroxyprogesterone acetate (MPA) and RU-486 (1 × 10(-11) and 1 × 10(-8) M) behaved as agonists activating extracellular signal-regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…*p<0.05, significantly different from control determined. A previous study indicated that membraneassociated PR is insensitive to the negative regulatory effect of antiprogestins [47], thus it is possible that membraneassociated PR mediates MPA-dependent down-regulation of RANKL. Moreover, the effect of progestin-dependent RANKL on human breast cancer progression is controversial [48], and it is possible that progestin regulates expression of RANKL via different mechanisms in murine and human mammary cells [49].…”
Section: Discussionmentioning
confidence: 98%
“…*p<0.05, significantly different from control determined. A previous study indicated that membraneassociated PR is insensitive to the negative regulatory effect of antiprogestins [47], thus it is possible that membraneassociated PR mediates MPA-dependent down-regulation of RANKL. Moreover, the effect of progestin-dependent RANKL on human breast cancer progression is controversial [48], and it is possible that progestin regulates expression of RANKL via different mechanisms in murine and human mammary cells [49].…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, the lack of MPA activity is difficult to reconcile with a nPR-dependent mechanism because MPA has high binding affinity for the nPR and activates it (58). Finally, the finding that progesterone acts at the cell surface to increase NO production is not consistent with an involvement of the nPR because to date clear evidence that the nPR is expressed on the cell surface has been obtained for only a few types of vertebrate cells (5). Although Boonyaratanakornkit et al (4) unambiguously demonstrated that progesterone rapidly activates intracellular signaling through the nPR in an extranuclear location in breast cancer cells, they could not detect nPR by ICC on the plasma membranes of any of the cell types they examined (3).…”
Section: Discussionmentioning
confidence: 99%
“…The human epidermal growth factor receptor 2 (HER2) is also overexpressed in 20% of breast tumors, most of which are hormone receptor-negative [1]. These three receptors offer defined therapeutic targets, such as is the case with tamoxifen and trastuzumab [1, 2]. However, about 15% of breast cancers lack estrogen and progesterone receptors as well as HER2, representing an aggressive and heterogeneous subtype group known as triple-negative breast cancer (TNBC) [1].…”
Section: Introductionmentioning
confidence: 99%